Identification and Mapping of Request-Offer Commodity Exports under the Indonesia–Sri Lanka Trade Cooperation Initiative (PTA) - Hotsawadi; Widyastutik; Nuzilia (Buletin Ilmiah Litbang Perdagangan, 2025)
Indonesia’s low ranking as an exporter to Sri Lanka indicates the need for a strategy that is more focused on improving the competitiveness of commodities, one of which is through the utilization of opportunities currently being initiated via bilateral trade cooperation schemes. This study aims to identify, map, and measure the export performance of request-offer commodities under the bilateral trade cooperation framework between Indonesia and Sri Lanka (PTA). The analytical methods used include export market share, the RCA index, the X-Model, EPD, the Frequency Index, and the Coverage Ratio of Non-Tariff Measures (NTMs). The results show that the export performance of the 20 initially proposed “request” commodities shifted from a “falling star” (55%) and “retreat” (45%) position to a “falling star” (5%) and “retreat” (95%) position from 2018 to 2022. From the perspective of the X-Model analysis, the market development performance of these requested commodities—which was 55% in the “potential market development” category and 45% in the “less potential market development” category—shifted to 100% in the “less potential market development” category from 2018 to 2022. The results of the analysis using the FR and CR approaches show that, collectively, 100 percent of Indonesia’s sixteen requested commodities are still subject to at least one NTM barrier imposed by Sri Lanka. Nevertheless, commodities originating from Indonesia still tend to have higher competitive potential compared to products from competing countries.